Information system of Limboto Lake potential management - Lanto Ningrayati Amali; Sunarty Eraku; Ishak Isa; Rifadli Bahsuan; Sitti Suhada; Muhammad Rifai Katili (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Limboto Lake is one of the lakes in Gorontalo Province; its water supply is generated from 23 small and large rivers. The lake holds potential in several sectors, e.g., tourism, fisheries, socio-economy and culture. However, such an advantage has no quality information system as it is found that there are no particular services that manage the information regarding Limboto Lake accurately. The objective of this research is to create an information system for the management of the potential area of the lake to provide quality services to access the information accurately and completely. The provided information is also updated timely. This research employed the System Development Life Cycle (SDLC) method in the development of the information system. Furthermore, the data were collected from interview, observation, and reviewing literature and document. This system is tested using white box and black box where it generated the expected outcome and is web-based. The output of this research is a system that eases the society to access the information regarding the management of the potential area in Limboto Lake.